2005
DOI: 10.1088/0960-1317/15/12/018
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of a micromachined force gauge under uncertainty

Abstract: Micromachined force gauges, like many microdevices, are subject to inevitable and inherent uncertainty in dimensional and material parameters that lead to variability in the gauge accuracy and reliability. This paper presents a methodology for the design of a micromachined force gauge under uncertainty, in which the measured force and the maximum stress in the beams in the gauge are related to five uncertain design parameters representing the dimensions of the beam, the material property and the deflection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For example, for silicon tuning fork commercial gyroscopes, it was shown in [ 6 ] that, in order to obtain a sense-drive frequency separation accuracy on the order of 2%, fabrication tolerances for critical suspension springs had to be close to the limit of the deep reactive-ion etching (DRIE) technology. Similarly, in [ 7 , 8 ], it was shown that, in order to make monolithically integrated microtensile testers, the role of uncertainties in the stiffness of critical MEMS components can become considerable.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for silicon tuning fork commercial gyroscopes, it was shown in [ 6 ] that, in order to obtain a sense-drive frequency separation accuracy on the order of 2%, fabrication tolerances for critical suspension springs had to be close to the limit of the deep reactive-ion etching (DRIE) technology. Similarly, in [ 7 , 8 ], it was shown that, in order to make monolithically integrated microtensile testers, the role of uncertainties in the stiffness of critical MEMS components can become considerable.…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to their small size of typically a few hundreds of microns in length and a few tens of microns in width, AFM probes are not convenient for force calibration of commercial tactile probing tools. Furthermore, by increasing the cantilever length with respect to typical AFM probes both reliability and accuracy can be improved (Mawardi and Pitchumani 2005). Therefore, transfer standards based on silicon microcantilevers with optimized dimensions have been developed as well as calibration procedures operating the transfer standard both as stiffness artifact and as load cell (Behrens et al 2003).…”
Section: Introductionmentioning
confidence: 99%